HALAL TOURISM IN THAILAND: BETWEEN POLITICAL ECONOMY AND GOVERNMENT CONCERN - Nurul Husna; Risatul kautsari; Andi Faradiba Irfan (International Journal of Sharia Studies, 2023)
Halal tourism is an income source in a number of Muslim countries. It's just that the halal tourism trend is also emerging in Muslim minority countries such as Thailand. Currently Thailnd is developing a halal tourism project with various products, such as providing sharia hotels, and halal food menus since being on airlines such as: Thai Airways. The critical question examined in this research is whether efforts to develop halal products and sharia banking are a government concern for Islamic law, or are they merely political-economic interests to reap financial benefits from Muslim consumers. This research uses a qualitative approach, sourced from online literature, journals and websites that are relevant to halal tourism studies. In this way, this article can see the extent to which the halal tourism policy is being implemented in Thailand, and its impact on the tourism sector. The results of this research show that the Thai government is pursuing halal tourism not because they are concerned about Islamic law, but only for the benefit and political-economic interests.